IMPACT OF DISCIPLINE AND MOTIVATION TOWARD RADIOTHERAPY INSTALLATION EMPLOYEES PERFORMANCE AT RSUD Dr. H. ABDUL MOELOEK LAMPUNG PROVINCE - Ahmad Hudalil; M Rafieq; Trisnowati Josiah (University of Sang Bumi Ruwa Jurai, 2021)
The research was conducted at RSUD Dr. H. Abdul Moeloek Hospital Lampung Province. This study used 18 respondents. The variables in this study are: 2 (two) independent variables (X1 and X2) and 1 (one) dependent variable where discipline (X1) and motivation (X2) are independent variables and employee performance (Y) is the dependent variable. Quantitative analysis uses a simple regression equation with partial hypothesis testing using the T test, and multiple linear regression equations with partial hypothesis testing using the F test. From the results of data processing, it has been found that the answers to the hypothesis are as follows; there was influence of discipline (X1) on employee performance (Y), with a level of influence (R-square) of 73.0%, which means that discipline has an effect of 73.0% on employee performance. There was influence of motivation (X2) on employee performance (Y), with a level of influence of 48.6% which means that motivation has an influence of 48.6% on employee performance. There was influence of discipline (X1), motivation (X2) on employee performance (Y), with an influence level of 81.0% which means that discipline and motivation have an influence of 81.0% on employee performance.